Oral Candida Albicans Colonization In Denture Wearer: A Literature Review - Febriane Balafif, Felisha; Rafisa, Anggun; Kuswandani, Faisal; Najmi, Nuroh (Jurnal EduHealth, 2024)
Denture stomatitis is the most prevalent multifactorial, chronic inflammatory oral condition amongs denture wearers. One of the primary roles of dentures in denture stomatitis is their potential to cause irritation and inflammation of the oral tissues. This continuous irritation creates an environment where fungal infections, notably C. albicans. The traumatic factors such as mechanical trauma caused by loose prosthesis can increase the risk of tissue penetration and colonization of Candida species. This literature review aimed to explore the colonization of C. albicans in the denture wearer. The article was conducted of two databases and were limited to the period from 2019 to 2024 with a combination of the following keywords: “oral Candida albicans” "colonization" "denture wearer". The results obtained A total of 243 articles were initially identified through the designated keywords in PubMed and Google scholar. After meticulous removal of duplicate articles and application of the inclusion and exclusion criteria, 7 articles met the study’s eligibility criteria. C. albicans was the predominant species recovered from oral caviproty of both denture wearers and non-denture wearers. C. albicans can not only adhere to the oral mucosa but also can colonize the surface of the acrylic denture when it is poorly maintained. The presence of prosthetic appliances changes the microenvironment of the oral cavity through the facilitation of Candida colonization and proliferation. The biofilm on the denture can enhance its adhesion adding to its virulence. Wearing of a denture has been found to enhance adhesion of C. albicans.